Quantifying Benefits Of Lean Manufacturing Tools Implementation With Simulation In Coolant Hose Factory - Mohamad, Effendi (Penerbit Universiti, Universiti Teknikal Malaysia Melaka, 2013)
Lean Manufacturing (LM) is a philosophy aiming at detecting and eliminating waste throughout a product’s value stream by means of a set of synergistic tools and techniques. Examples of LM tools and techniques are Single Minute Exchange of Die (SMED), Kanban, 5’S, Value Stream Mapping(VSM), Preventive Maintenance(PM), Cellular Manufacturing (CM), Standardised Work, Heijunka, and Poka Yoke. Although these tools could resolve many manufacturing issues, it is difficult to quantify the benefits of implementing LM before implementation. Therefore, this study focused on a process simulation approach to observe the effectiveness of LM tools before their implementation. A process model of a Coolant Hose Manufacturing (CHM) factory was designed and its simulation model was then implemented. Subsequently, this paper presents the implemented simulation model and shows how it could be used to see the effect of LM tools using an example of SMED LM tool and CM LM tool.